PENGARUH HUMAN RELATION, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. SUKSES MITRA SEJAHTERA - Rofiq, Fadya Berlianna (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The success of a company can be created by the productivity of employees. To achieve employee productivity, it is necessary to have an understanding of employee motivation. Establishing a good relationship between employees and superiors is very important, this can avoid conflict so as to create a harmonious relationship between employees and superiors. Like the problems that exist in PT. Sukses Mitra Sejahtera, regarding rejected goods that previously reached the number 5, which means very bad. Because the superiors provide clear information, daily work targets, what needs to be considered while working, and provide encouragement. The goal of the study was to ascertain how employee productivity at PT. Sukses Mitra Sejahtera was impacted by interpersonal relationships, workplace motivation, and surroundings. Because the measurement of this variable takes the form of numbers that can be examined using statistics and SPSS, this study adopts a quantitative methodology. This method goes through multiple stages, including data collection through questionnaires, data analysis, and hypothesis testing. In this study, 93 participants made up the sample, and total sampling was the sampling method.